(untitled) (Andamios, Revista de Investigación Social, 2024)
In this research we defend the thesis that Ignacio Ellacuría’s project of philosophy of liberation does not represent a rupture with the metaphysical theses of his teacher Xavier Zubiri. From our perspective, this aspect is particularly evident in the category of real truth. Therefore, we propose an approach to this category in Ellacuría’s thought in two moments. First, we analyze the reception of real truth in Ellacuría, emphasizing aspects such as its link with the impression of reality, its historical dimension and its role in shaping human reality. In a second moment we demonstrate how in the context of historical reality this notion is directly related to the fundamentality, discernment and liberating function of philosophy. We end with the elucidation of some conclusions on this subject.